Pendampingan Usahatani Jagung Pakan dan Kedelai Edamame pada Ponpes Nurul Muhibbin, Kalimantan Selatan - Agung Nugroho; Joko Purnomo; Riza Adrianoor Saputra; Untung Santoso; Jumar Jumar; Muhammad Imam Nugraha; Qudsi Ramadani; Muhammad Ronny Hakim; Lukman Nol Hakim; Noni Septiana; Rifqi Rahman Sidik; Mislawati Mislawati; Saskia Nurlita (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Routine assistance to several Islamic boarding schools, including the Nurul Muhibbin Halong Islamic Boarding School, is the Adaro Santri Sejahtera (PASS) Program. This program focuses on skill development so that besides having religious knowledge, students are also expected to know about entrepreneurship. This mentoring activity is a form of Community Service (PkM) for Lambung Mangkurat University (ULM) as a driving effort to develop a business unit for cultivating and marketing community agricultural products, such as feed corn and organic edamame. This activity is also aimed at making Islamic boarding schools more prosperous, independent, and advanced in learning religious knowledge and providing students with knowledge and skills in agribusiness to become independent people. This activity was carried out for four months (August‒December 2021) at the Nurul Muhibbin Islamic Boarding School, Halong District, Balangan Regency, South Kalimantan, with a target number of participants of 20 people. The method used in this activity is a classical and individual approach. The classical approach was taken when providing theory regarding the introduction of feed corn cultivation and organic edamame, while the individual approach was taken when filling out the questionnaire. This service activity produces elements of Islamic boarding school students, caregivers, and congregation farmers who have knowledge, understanding, and skills in intensive feed corn and organic edamame cultivation. This is essential capital for the Islamic boarding school to continue and develop farming to create an independent Islamic boarding school.